Clinical phenotypes of COPD and health-related quality of life: a cross-sectional study - Chee-shee, Chai; Yong-Kek, Pang; Diana leh, -Ching ng; seng-Beng, Tan; Tat-seng, Wong; Jo-ee, sia (Dove Medical Press Limited., 2019)
The Spanish COPD guideline (GesEPOC) classifies COPD into four clinical phenotypes based on the exacerbation frequency and dominant clinical manifestations. In this study, we compared the disease-specific health-related quality of life (HRQoL) of patients with different clinical phenotypes.